Compositional effects on the electrical properties of extremely disordered molybdenum oxynitrides thin films - Hofer, J.A.; Bengio, S.; Rozas, G.; Pérez, P.D.; Sirena, M.; Suárez, S.; Haberkorn, N.; Haberkorn, Néstor (Elsevier, 2020)
Fil: Hofer, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina